Simulation analysis of lift in synchronized swimming - Nakashima, M.; Hatakeyama, G.; Homma, M.; Ito, K. (Journal of Aero Aqua Bio-mechanisms, 2014)
The simulation method for synchronized swimming was developed by extending the swimming human simulation model `SWUM.` In order to acquire the input data for the simulation, an experiment using subject swimmers was carried out. Using the acquired input data, the simulation reproducing the experiment was conducted. The simulated results were compared with the experimental ones and the sufficient validity of the simulation method was confirmed. In addition, parameter studies about timing of motion among the swimmers were conducted. It was found that the jumping height became maximum (0.7m larger than original) when the upper swimmer's motion was 0.07s earlier.